2014
DOI: 10.1016/j.ces.2014.05.054
|View full text |Cite
|
Sign up to set email alerts
|

Interception efficiency in two-dimensional flow past confined porous cylinders

Abstract: The flow interception efficiency, which provides a measure of the fraction of streamlines that intercept a porous collector, is an important parameter in applications such as particle capture, filtration, and sedimentation. In this work, flow permeation through a porous circular cylinder located symmetrically between two impermeable parallel plates is investigated numerically under different flow and geometrical conditions. A flow interception efficiency is defined and calculated based on the flow permeation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Examples include coal particles in power stations, suspended sediment in coastal waters, and catalyst clusters in fluidized bed reactors. The permeability of the particle can affect the flow pattern as well as particle-fluid interactions to various extents (Chen & Cai 1999;Bhattacharyya, Dhinakaran & Khalili 2006;Shahsavari, Wardle & McKinley 2014). Nonetheless, there have been no investigations about the rotation of porous particles in fluid flow, apart from a very recent theoretical analysis by Masoud, Stone & Shelley (2013) on the rotation of porous ellipsoids in an unbounded simple shear flow.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include coal particles in power stations, suspended sediment in coastal waters, and catalyst clusters in fluidized bed reactors. The permeability of the particle can affect the flow pattern as well as particle-fluid interactions to various extents (Chen & Cai 1999;Bhattacharyya, Dhinakaran & Khalili 2006;Shahsavari, Wardle & McKinley 2014). Nonetheless, there have been no investigations about the rotation of porous particles in fluid flow, apart from a very recent theoretical analysis by Masoud, Stone & Shelley (2013) on the rotation of porous ellipsoids in an unbounded simple shear flow.…”
Section: Introductionmentioning
confidence: 99%
“…While flow around solid objects is a popular problem in aerodynamics, flow around porous objects has only recently begun to be investigated within in the past few decades, using either high fidelity numerical simulation or experiments [78][79][80][81][82]. Here, we present an example of flow past a porous cylinder using the LBM.…”
Section: Flow Past a Porous Cylinder (Via Lattice Boltzmann)mentioning
confidence: 99%
“…Modeling has suggested that changing the CNT elements' geometry to optimize the flow interception at a given pressure drop and fluid volumetric flow rate enhances polymer and bioparticle interception with the CNT surfaces 67 . The recorded intensity via confocal imaging is likely to be conservative and may underestimate the count because of several factors: (1) Fabrication of the microfluidic devices requires inverted imaging, i.e., through the PDMS because of the opacity of silicon.…”
mentioning
confidence: 99%